Teaching Style, Digital Literacy, and Self-Efficacy on Early Childhood Education Teacher Capabilities - Sya’dullah, Achmad; Setyosari, Punaji; Ulfa, Saida; Praherdhiono, Henry; Saroinsong, Wulan Patria (Jurnal Pedagogi dan Pembelajaran, 2024)
Problems experienced by PAUD teachers during online learning are viewed from educational background, length of teaching and self-efficacy. The purpose of the study was to analyze the relationship between digital literacy (LD), teaching style (GM) and self-efficacy (ED) on the capabilities of PAUD teachers (KG) during the Covid 19 pandemic. This research is quantitative using the expost facto model to determine the causal relationship between events and conditions. The sample used proportional stratified random sampling of 355 teacher respondents with more than three years of teaching experience and a diverse educational background. The instrument used was a questionnaire with descriptive statistical analysis techniques and Structural Equation Modelling (SEM). We collected data through digital literacy questionnaire, teaching style scale, self-efficacy instrument and ECD teachers' capabilities. The study found that: 1) there is a relationship between LD and GM; 2) there is no relationship between LD and ECD KG; 3) there is a relationship between LD and ECD teachers' ED; 4) there is a relationship between GM and teachers' ED; 5) there is a relationship between GM and KG; 6) there is a relationship between ED and KG; 7) there is a relationship between LD and KG through ED; 8) there is no relationship between GM and KG through ED.